Race, religion, and law in colonial India trials of an interracial family - Mallampalli, Chandra, 1965- (Cambridge studies in Indian history and society ;, 2011)
"Through a landmark court case in mid-nineteenth century colonial India, this book investigates hierarchy and racial difference in the British encounter with Indian society"--